2019
DOI: 10.1038/s41598-019-41800-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of exosome isolation methods using culture supernatant for optimum yield, purity and downstream applications

Abstract: Exosomes have received significant attention for their role in pathobiological processes and are being explored as a tool for disease diagnosis and management. Consequently, various isolation methods based on different principles have been developed for exosome isolation. Here we compared the efficacy of four kits from Invitrogen, 101Bio, Wako and iZON along with conventional ultracentrifugation-based method for exosome yield, purity and quality. Cell culture supernatant was used as an abundant source of exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
376
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 432 publications
(391 citation statements)
references
References 32 publications
12
376
0
3
Order By: Relevance
“…22 For immunoblotting, total protein (10/40 µg) isolated in NP40 buffer supplemented with protease 1X PPI cocktail was loaded on to SDS-polyacrylamide gel and resolved by electrophoresis. 22 For immunoblotting, total protein (10/40 µg) isolated in NP40 buffer supplemented with protease 1X PPI cocktail was loaded on to SDS-polyacrylamide gel and resolved by electrophoresis.…”
Section: Protein Quantification and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…22 For immunoblotting, total protein (10/40 µg) isolated in NP40 buffer supplemented with protease 1X PPI cocktail was loaded on to SDS-polyacrylamide gel and resolved by electrophoresis. 22 For immunoblotting, total protein (10/40 µg) isolated in NP40 buffer supplemented with protease 1X PPI cocktail was loaded on to SDS-polyacrylamide gel and resolved by electrophoresis.…”
Section: Protein Quantification and Immunoblottingmentioning
confidence: 99%
“…Protein-based quantitation of isolated EV or cell lysates was done using the protein DC assay kit as described earlier. 22 For immunoblotting, total protein (10/40 µg) isolated in NP40 buffer supplemented with protease 1X PPI cocktail was loaded on to SDS-polyacrylamide gel and resolved by electrophoresis. Subsequently, resolved protein bands were transferred on to polyvinylidene difluoride membrane and probed with specific antibodies against thrombospondin (THBS1), ARF6, CD9, CD63, HIF-1α, and β-actin.…”
Section: Protein Quantification and Immunoblottingmentioning
confidence: 99%
“…Previous publications showed lower exosomal protein detection (e.g. CD63) by Western blot using the polymer-based precipitation compared to ultracentrifugation, despite observing a greater number of vesicles by NanoSight using polymer-based precipitation [28,38]. Based on these publications, we suspected that the polymer matrix was hiding epitopes.…”
Section: Optimization Of Muscle Exosome Extractionmentioning
confidence: 79%
“…Looking at the literature, we noticed that the polymer kit consistently led to a greater number of vesicles detected by NanoSight [49,52,56], and yet led to a reduced detection of exosomal markers by Western blot [28,38,49,52,56,57]. Interestingly, Rider et al, while optimizing a polymer to extract extracellular vesicles, showed that rinsing of exosomes that had been precipitated using the polymer resulted in an increase in exosome markers detected by Western blot [28].…”
Section: Resultsmentioning
confidence: 97%
“…This is a relatively simple process and does not require the use of specialized equipment. However, the use of foreign polymers can introduce impurities into the sample that is difficult to remove, and may adversely impact downstream applications [30,31]. A third method, immunoaffinity, relies on the interactions between exosome membrane proteins and their respective antibodies [29] This is a more precise method of capturing specifically exosomes, but is limited in that it cannot be used for large sample volumes.…”
Section: Exosome Isolation and Characterizationmentioning
confidence: 99%